Seroprevalence of HBV, HCV and HIV infections in blood donors in voluntary and replacement donors in a tertiary care hospital in Western Uttar Pradesh, India - Dr. Tandra Chadha; Dr. Shashikant Adlekha (Tropical Journal of Pathology and Microbiology, 2018)
Background: The World Health Organization recommends universal and quality-controlled screening of blood donations for the major transfusion-transmissible infections (TTIs): human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and syphilis. The magnitude of transfusion-transmitted infections (TTI) varies from country to country depending on TTI’s load in that particular population. The present study was undertaken to determine the relative proportion of voluntary donors (VDs) and replacement donors (RDs) and also, to estimate and compare the seroprevalence and changing trends of TTIs amongst VDs and RDs in a tertiary care medical hospital in north India. Methods: This retrospective study was based on the records of all voluntary and replacement donations whichwere collected from January 2016to August 2018 in atertiary care medical college and hospital in Bareilly, Uttar Pradesh, India. Results:Of the total 7908 donations, 2268 (28.6%) were voluntary and 5640 (71.4%) werereplacement donation. The overall seroprevalence of TTI was 158 (1.9%) out of total 7908 donations, with prevalence ofhepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV), were 1.0, 0.8 and 0.1 percent, respectively. Furthermore, the TTIs were more frequently encountered in RDs in comparison to VDs. Conclusions: The potential risk of TTIS can be curtailed to a large extent by increasing in public awareness regarding voluntary blood donation, donor screening using stringent criteria, counselling anduse of highly sensitive and specific tests.